Mise En Évidence De Nouvelles Structures Géologiques Dans La Région De Brobo (Centre De La Côte d’Ivoire). Aide À La Compréhension De La Tectonique Du Paléoprotérozoïque Du Craton Ouest Africain - Mathurin, Daï Bi Seydou; Gbele, Ouattara; Barthélémy, Koffi Gnammytchet; Allou, Gnanzou; Inza, Coulibaly (European Scientific Journal, ESJ, 2018)
The lithological and structural observations of the region of Brobo (Central Côte d’Ivoire) indicate a succession of metasedimentary rocks (micaschists with cordierite, silstones, graphitic sediments, sandstones with amphibole-garnet, etc.) intermixed with volcanic rocks (rhyolite, dacite, andesite, basalt and the volcanoclastics). The whole is intruded by granites with one or two micas, sometimes porphyries, granodiorites, gabbros, and granite gneisses. Interpretations of Landsat ETM+ , RadarSat-1 and SRTM remote sensing imageries, as well as field data, revealed several lineament directions which, after field control, correspond to major faults and shear zones. These large structures show the N-S, NE-SW, NNE-SSW, E-W, NWSE, and NNW-SSE orientations. The field data also made it possible to describe several structures and to propose a preliminary geodynamic model for the setting and structuring of the formations of this region. This model suggests that the geodynamic took place in three stages: distension with a deformation of basement formations generating a gneissocity (D1), as well as deposits of sediments in the basins; followed by a NW-SE to E-W convergence generating a cleavage in the volcanogenic series (D2). This phase of deformation continues while creating, locally, a strain slip cleavage or a transposed schistosity. The third cleavage affects the volcanogenic series (fractures cleavages, D3) and ends in large corridors of ductile shear zones and associated faults.